Głusi jako społeczność posiadająca własną tożsamość kulturową: przegląd literatury - Bączyk, Martyna (Studia Edukacyjne, 2024)
The Deaf Community is a distinct and unique linguistic minority. The article describes this group as collectivist and with its own cultural identity, based on Polish and international literature. Indicating the characteristics of this group and its members, the text shows how it works in Poland and Germany. It points to the many interesting initiatives and associations run by members of the Deaf Community.